Assessment of macrophage and granulocyte cell-enhanced phagocytosis of Mycobacterium tuberculosis - Fourie, Bernard P. (University of Pretoria, 2021)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2020.